Efeito da Administração Oral do Extrato de Baccharis dracunculifolia na obesidade induzida por Glutamato Monossódico (MSG) - Hocayen, Palloma de Almeida Soares (2012)
In recent years diabetes has been gaining huge proportions, due to changes in the habits of life, poor diet and physical inactivity are key factors in disease development. To this end, various species of plants have been used etnofarmacologicamente or in clinical trials or to treat and combat the symptoms of Diabetes Mellitus. The present study used the methanol extract of the plant Bracharis dracunculifolia (rosemary field) belonging to the Asteraceae family, with the objective of evaluating the effect of his administration on hypothalamic obesity in animal model of MSG. The methodology was based on the preparation of the extract metabolic B. dracunculifolia by means of drying processes, spraying, orbital agitation of the extract in methanol, filtration and addition of rotaevaporação toxicity test of the extract in the brine shrimp. To obtain MSG animals, were used in newborn animals still injection of monosodium glutamate (MSG) for five consecutive days at a dose of 4 mg / g body weight to induce obesity. Treatment with methanol extract was carried out on animals at 180 days of life, for 30 days. Weight was evaluated, consumption of water and feed throughout the experiment. And after the animals have been sacrificed held in the isolation of pancreatic islets which were incubated with increasing concentrations of glucose (5.6 mM, 8.3 mM, 16.7 mM). The results obtained in the study demonstrated low toxicity of the extract of B. dracunculifolia. The MSG animals had proven by induction of obesity increased Lee index, and higher levels of visceral and subcutaneous fat compared to controls. The MSG animals weighed less, consumed less water and less food and had impaired glucose tolerance. The biochemical parameters did not obtain significant differences, except for triglycerides which showed to be higher in MSG animals, not having succeeded in restoring the extract this parameter. In the isolation of pancreatic islets, MSG animals that received the extract of B. dracunculifolia showed a significant secretion of insulin by the islets isolated, noting that the concentration of 8.3 mM and 16.7 mM was obtained increased secretion of insulin. It is concluded that the methanol extract of B. dracunculifolia obtained significant effect on insulin secretion in pancreatic islet cell isolation, noting the results obtained in the group MSG (MP), which were hyperinsulinemia because of a possible enhancement of oxidative stress, especially the high antioxidant content present in the extract B. dracunculifolia used in the study.